TANTANGAN DAN PROSPEK PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI UNIRA - HARIRI, MOH; Maimun, Maimun; Toha, Toha; Ridho, Ali (IAIN Bone, 2024)
The development of education, particularly in Islamic Religious Education (PAI), is crucial in shaping individual personalities and strengthening Islamic identity within the community. At public universities (PTUs) like the University of Madura (UNIRA), developing the PAI curriculum is essential to respond to changing times and advancing knowledge. Challenges include integrating Islamic values with modern knowledge, adapting to technological advancements in learning, and enhancing students' understanding of religious education. This research employs a descriptive qualitative method through interviews, observations, and documentation with 20 students and PAI lecturers at UNIRA. Findings reveal several key issues, such as the minimal PAI credit load of only 2 credits, lack of student enthusiasm for PAI subjects, variations in PAI development, and challenges in the quality of teaching staff and a supportive campus environment for religious learning. The development of the PAI curriculum at UNIRA should aim to shape students of character and integrity, capable of positively contributing to society. Innovations in teaching methods, strengthening collaboration with Islamic institutions and academics, and industry cooperation are opportunities to explore. This implementation aims to make PAI relevant to modern life needs and equip students to face changing times.